Peran Dinas Kelautan dan Perikanan Provinsi Sumatera Barat dalam Meningkatkan Kapasitas Penangkapan Ikan dan Kesejahteraan Nelayan Sumatera Barat - Jihan Anfiska; Aldri Frinaldi (PT Ilmu Data Indonesia, 2026)
The marine and fisheries sector plays a strategic role in supporting food security and the coastal economy in Padang City. However, small-scale fishermen still face limitations in operational capacity and socio-economic vulnerabilities. This study aims to analyze the effectiveness of the fishing capacity building and fishermen empowerment programs implemented by the Marine Affairs and Fisheries Department (DKP) of West Sumatra Province in Padang City. A qualitative-descriptive approach was employed in this research. Data were gathered through in-depth interviews with DKP officials and fishermen group leaders, field observations in Bungus Teluk Kabung, Pasia Nan Tigo, and Pasia Jambak, as well as document analysis of vessel inspection records from 2021 to 2025. The results indicate that the distribution of production aids (outboard engines, boats, nets, and fishboxes) effectively expanded fishing grounds and preserved catch quality. Nevertheless, administrative compliance remains a challenge, with 12.06% of inspected vessels lacking complete permits, potentially driving illegal fishing practices. Furthermore, a welfare gap persists due to climate fluctuations and high operational costs. It is concluded that empowering fishermen requires more than physical assistance; it demands institutional strengthening, access to formal capital, and continuous mentoring.